Pengukuran Indeks Kepuasan Masyarakat (IKM) Kader Posyandu Mawar Terhadap "Program Duta Bahtera" CSR PT Pertamina Patra Niaga AFT Syamsudin Noor - Faidah Ramadhani (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
PT Pertamina Patra Niaga AFT Syamsudin Noor as a company operating in aviation fuel services, is committed to acting ethically in running its business. One of them is by running an empowerment program that targets the community in the company's ring-1 area. AFT Syamsudin Noor has five CSR programs that cover aspects of community empowerment, capacity building and infrastructure improvement. The five programs are Duta Bahtera (Posyandu Pertamina Bahagia and Sejahtera), Hiling di Kasturi (Greening and Environmental Management in RT 33 Kasturi), Pertamina Sigana (Disaster Preparedness), Sambar Deer Conservation and Endemic Kalimantan Plants and the Eco Green School Program. All of these programs have started since 2022, except for the conservation program which started since 2019.